Artificial Metalloenzymes on the Verge of New-to-Nature Metabolism. Issue 1 (January 2018) - Jeschek, Markus; Panke, Sven; Ward, Thomas R.
Abstract : Residing at the interface of chemistry and biotechnology, artificial metalloenzymes (ArMs) offer an attractive technology to combine the versatile reaction repertoire of transition metal catalysts with the exquisite catalytic features of enzymes. While earlier efforts in this field predominantly comprised studies in well-defined test-tube environments, a trend towards exploiting ArMs in more complex environments has recently emerged. Integration of these artificial biocatalysts in enzymatic cascades and using them in whole-cell biotransformations and in vivo opens up entirely novel prospects for both preparative chemistry and synthetic biology. We highlight selected recent developments with a particular focus on challenges and opportunities in the in vivo application of ArMs. Trends: ArMs are an emerging form of non-natural biocatalysts that can create biocatalytic novelty with potential applications in preparative chemistry and synthetic biology. Initial engineering efforts for ArM creation have been conducted in well-defined in vitro systems based on purified protein variants, and therefore systematic directed evolution of ArMs as well as their introduction into cellular pathways have hitherto been largely limited. More recently, a trend towards using ArMs in whole-cell systems and in vivo has emerged, which is associated with several key obstacles that remain to be overcome. This transition shows great promise for the sustainable production of commodity chemicals and new-to-nature metabolites using ArMs.